Alpha-thalassemia due to the deletion of nucleotides -2 and -3 preceding the AUG initiation codon affects translation efficiency both in vitro and in vivo. - Morle, F (1986)
We previously hypothesized that a 2 nucleotide deletion, causing a A-greater than C change at position -3 preceding the ATG initiation codon of alpha globin gene, reduced translation efficiency of alpha globin mRNA and was responsible for a form of alpha + thalassemia displayed by an Algerian patient. We presently show that this deletion leads to a 30-45% reduction in translation efficiency of synthetic alpha globin mRNA in rabbit reticulocyte lysate. In other experiments, we constructed alpha/G gamma hybrid globin genes in which the 3' end of normal or mutated alpha globin genes downstream to the ATG initiation codon was substituted by the 3' part of a G gamma globin gene. COS cells transfected with either of these 2 hybrid genes were shown to synthesize a similar amount of alpha/G gamma hybrid mRNAs but 50% less G gamma globin when transfected with the alpha/G gamma hybrid gene carrying the deletion. These results definitively establish that the 2 nucleotide deletion reduces translation efficiency by 30-50%. This contrasts with the 93% reduction induced by a similar A-greater than C change at position -3 in the different nucleotide context preceding the ATG codon of the rat preproinsulin gene.